CaTe: a new topological node-line and Dirac semimetal - Yongping Du (Nature Portfolio, 2017)
Topological physics: a predicted node-line semimetal CaTe Topological insulators are materials with non-trivial topological order that are insulating in their bulk but conductive on their surface. Recent findings extend the topological states to three-dimensional semimetals that host exotic physical phenomena such as Weyl fermion quantum transport and Hall effects. Among the three types of topological semimetals, three-dimensional Dirac semimetals evolve to Weyl analogs upon breaking of time reversal or inversion symmetry. Here, the theoretical work by a team led by Professor Xiangang Wan from Nanjing University in China proposes a new phase that falls into the third category: node-line semimetals. Based on first-principles calculations and effective model analysis, CsCl structured CaTe is predicted to be a node-line semimetals with characteristic drumhead-like surface states if spin-orbit coupling is absent. When spin-orbit coupling is included, CaTe becomes a three-dimensional Dirac semimetal.